La Recreación activa en el desarrollo socio afectivo de los niños del subnivel II, en la Escuela de Educación Básica General Juan Lavalle, de la Ciudad de Riobamba Provincia de Chimborazo. Periodo Octubre 2020 - Marzo 2021 - Bastidas Caceres, Jesica Alexandra (2021)
Currently, society dictates the norms, attitudes, and values to guide the child's affective development and learning patterns. Therefore, affective growth is a necessary process to take into account from an early age. Various scientific advances put emotional intelligence at the forefront, but few delve into the little ones' affective capacities. For affective development to reach its fullness in sublevel children, their abilities, such as self-knowledge and detection and the regulation of their own emotions, must be enhanced. This research tries to determine how active recreation helps in the socio-affective children's development through a methodology of a mixed approach, of descriptive scope, through synthetic, analytical methods, resulting in the proposal and design of an active recreation strategy to develop the socio-affective level in the Sub-level II children. Concluding that socio-affective development in early childhood education is essential, it is possible to sow and create that type of citizen capable of subsisting in an increasingly globalized world. Likewise, early childhood educators must not forget that they work with people. It depends on teaching technical learning, global learning, where the affective side contributes to the child's education.